Nickel cobalt sulfide Nanotube Array on Nickel Foam as Anode Material for Advanced Lithium-Ion Batteries. (20th April 2016) - Yu, D.J.; Yuan, Y.F.; Zhang, D.; Yin, S.M.; Lin, J.X.; Rong, Z.; Yang, J.L.; Chen, Y.B.; Guo, S.Y.
Abstract: A facile twice-hydrothermal method is developed for large-scale growth of NiCo2 S4 nanotube array on Ni foam with robust adhesion. As-prepared materials are characterized by SEM, XRD and EDS. It can be observed that NiCo2 S4 nanotubes directly grow on Ni foam with an average inner-diameter of ∼ 55 nm, external-diameter of 100 nm, and length of ∼ 2 μm. When evaluated as a binder-free anode for LIBs, NiCo2 S4 nanotube array exhibits outstanding lithium-storage performance that includes high special capacity, excellent cyclic stability and desirable rate capability. At 0.2 C rate, NiCo2 S4 nanotube array delivers the average discharge capacity of 720 mAh g −1 during 50 cycles that slightly surpasses its theoretical capacity of 703 mAh g −1 . When the current comes back to 0.2 C after rate measurements, NiCo2 S4 nanotubes can still stably deliver the discharging capacity of 652 mAh g −1, reaching 92.7% of that at the initial 0.2 C. Cyclic Voltammetry (CV) measurements reveal that NiCo2 S4 nanotube array contains two sets of electrochemical reaction behavior come from Ni and Co. The unique NiCo2 S4 nanotube array exhibits great potential as an anode material for high-performance Lithium-ion batteries.